Optimasi Suhu dan Waktu Ekstraksi Kulit Kayu Manis (Cinnamomum burmanii) dengan Gelombang Ultrasonik Menggunakan Response Surface Methodology (Rsm) - Diah Rupini, Ni Luh Putu; Rai Widarta, I Wayan; Kencana Putra, I Nengah (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 1 (2017), 2017)
Cinnamon is a spice containing components of volatile oil, non-volatile oil and starch. Thisstudy was aimed to determine the temperature and extraction time of cinnamon bark(Cinnamomum burmanii) with optimum ultrasonic waves, so as to produce oleoresin.Optimization of the temperature and extraction time of cinnamon bark was done by usingResponse Surface Methodology. The design of central composite was used to study theeffects of temperature and time on the extraction of cinnamon bark with ultrasonic waves.The results showed that the temperature of 58,3C and 77,7 minutes extraction of cinnamonbark with ultrasonic waves produced oleoresin yield; and the highest content ofcinnamaldehyd of cinnamon bark respectively 26,5770% and 1,7280%. Meanwhile, thevalue of the refractive index is equal to 1,5750 and the density is equal to 1,0360 g/cm3.
Keywords: cinnamon bark (Cinnamomum burmanii); temperature; time; ultrasonic waves; cinnamaldehyd